2010
DOI: 10.1007/s00795-009-0487-2
|View full text |Cite
|
Sign up to set email alerts
|

Detection of characteristic distributions of phospholipid head groups and fatty acids on neurite surface by time-of-flight secondary ion mass spectrometry

Abstract: Neurons have a large surface because of their long and thin neurites. This surface is composed of a lipid bilayer. Lipids have not been actively investigated so far because of some technical difficulties, although evidence from cell biology is emerging that lipids contain valuable information about their roles in the central nervous system. Recent progress in techniques, e.g., mass spectrometry, opens a new epoch of lipid research. We show herein the characteristic localization of phospholipid components in ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…The authors demonstrated the distribution of small lipids (lower than m/z 800) with high spatial resolution in some dystrophic tissue and obese model mice [13,14]. TOF-SIMS is a superior tool for highspatial-resolution IMS (submicron order) of elements and small molecules at different organelle levels of the cell [15]. However, due to the in-source fragmentation and the lack of tandem mass spectrometric facility, SIMS lacks sensitivity for the mass range over m/z 800 and the ability to identify molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The authors demonstrated the distribution of small lipids (lower than m/z 800) with high spatial resolution in some dystrophic tissue and obese model mice [13,14]. TOF-SIMS is a superior tool for highspatial-resolution IMS (submicron order) of elements and small molecules at different organelle levels of the cell [15]. However, due to the in-source fragmentation and the lack of tandem mass spectrometric facility, SIMS lacks sensitivity for the mass range over m/z 800 and the ability to identify molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Although the range of biochemical effects of PC (diacyl 16:0/20:4) is uncertain, elevated levels of the molecule have been reported in mammalian tissues with chronic inflammation. 3,4 We observed that PC (diacyl 16:0/20:4) contains arachidonic acid, which is a precursor to lipid mediators such as proinflammatory prostaglandins and leukotrienes. Taken together, these data indicate that the elevated tissue content of PC (diacyl 16:0/20:4) may be associated with chronic inflammation in the incompetent GSV.…”
Section: Discussionmentioning
confidence: 99%
“…1 IMS revealed the accumulation of lysophosphatidylcholine (LPC; 1-acyl 16:0) and phosphatidylcholine (PC; diacyl 16:0/20:4) in the valvular region. Because these molecules are potential proinflammatory lipids, [2][3][4] this finding suggests that LPC and PC are involved in the development of tissue inflammation and valvular incompetence. These results support previously reported data.…”
mentioning
confidence: 99%
“…They showed that vita-*Correspondence: fujiin@tmu.ac.jp min E and phosphatidylinositols concentrated within the cells, whereas intact phosphocholines accumulated over the most damaged areas of dystrophic muscle, together with cholesterol and sphingomyelin (SM) species. TOF-SIMS is an excellent tool for high-spatial-resolution IMS (submicron order) of elements and small molecules at different organelle levels of the cell 17) . However, due to in-source fragmentation and the lack of tandem mass spectrometric facility to identify the structure, SIMS lacks sensitivity for the mass range over m/z 800 and the ability to identify molecules.…”
Section: Application Of Ims To Skeletal Musclementioning
confidence: 99%